Translation, cross-cultural adaptation, and psychometric properties of the Finnish version of the Malocclusion Impact Questionnaire (MIQ) - Lucas Arrais Campos; Terhi Kaikkonen; Kaisa Ylitervo; Leena Ylikontiola; Anna- Sofia Silvola (Acta Odontologica Scandinavica)
Objectives: This study aimed to translate and adapt the Malocclusion Impact Questionnaire (MIQ) into Finnish; to estimate its psychometric properties when applied to Finnish adolescents; and to estimate the effect of demographic characteristics on the perceived impact of malocclusion.